Brain and Machine: Minding the Transhuman Future - Spezio, Michael L. (Dialog, 2005)
Ethical deliberations about brain-machine interfaces (BMI) focus on how humanity will be changed in imagined future transhuman landscapes. I review some current developments in BMI and suggest that responsible deliberation about BMI proceed by recognizing the typically implicit central role given to the imagined futures and the humans who inhabit them. As responsible deliberators about BMI, we make choices when we engage in “minding the other” that precede and constrain the choices we then make about BMI. I suggest possibilities for such minding that emerge from a theoanthropology grounded in the analogia relationis and that connect to a growing program of neurophenomenology.